The Impact of Audit Findings and Recommendation Follow-Up on Public Service Quality: An Empirical Investigation - Yanti, Harti Budi; Ardlillah, Barlian Izza (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024)DO - 10.24843/JIAB.2024.v19.i02.p06, 2024)
Public services, traditionally provided by government agencies, present challenges in measuring their quality. As a result, research on public service quality remains relatively limited. This study seeks to examine both the direct and indirect effects of audit findings and the follow-up of audit recommendations on public service quality. The analysis covers 480 regency and city governments over the period 2021–2022, employing panel data regression, ordinal logistic regression, and the Sobel test. The findings reveal that audit findings negatively affect public service quality, while the follow-up on audit recommendations has a positive impact. These effects are observed both directly and indirectly, mediated by the quality of financial statements. This underscores the critical role of sound financial management in delivering high-quality public services. The results suggest that government agencies should not only strive for unqualified audit opinions but also prioritize the thorough follow-up of audit findings and recommendations. Doing so enhances both the quality of financial reporting and the overall delivery of public services. Keywords : Public Service, Opinion, Audit Findings, Audit Recommendations Follow-up